Snow-Cover Variability in North America in the 2000-2001 Winter as Determined from MODIS Snow Products - Salomonson, Vincent V.; Hall, Dorothy K.; Chien, Y. L.; Riggs, George A.; Houser, Paul R. (2001)
Moderate Resolution Imaging Spectroradiometer (MODIS) snow-cover maps have been available since September 13, 2000. These products, at 500-m spatial resolution, are available through the National Snow and Ice Data Center Distributed Active Archive Center in Boulder, Colorado. By the 2001-02 winter, 5-km climate-modeling grid (CMG) products will be available for presentation of global views of snow cover and for use in climate models. All MODIS snow-cover products are produced from automated algorithms that map snow in an objective manner. In this paper, we describe the MODIS snow products, and show snow maps from the fall of 2000 in North America.